Customer analytics in Iceland : attitudes and implementation - Rúrik Karl Björnsson 1987- (2014)
Analytics are incresingly becoming a hot topic in businesses around the world. More and more companies are implementing analytics to stay ahead of the competition and at the same time increase knowledge of their customer base and market environment. The author was interested in researching how analytics were being implemented in the Icelandic market. Not much is known about how Icelandic companies are using analytics. The author decided to conduct in-depth interviews with twelve companies to learn more about the issue. Learn about attitudes towards analytics and how analytics are being implemented in the market. Interviews were recorded and responses analysed afterwards. The method of the research is discussed and key results presented.